Welcome to AI your personal guide to artificial intelligence - Shrier, David L. (Ascent Audio, 2024)
A fascinating guide to the rapidly advancing world of artificial intelligence and how this powerful technology will impact our lives, our careers, and our world. Artificial intelligence is driving workforce disruption on a scale not seen since the Industrial Revolution. In schools and universities AI technology has forced a reevaluation of the way students are taught and assessed. Meanwhile, ChatGPT has become a cultural phenomenon, reaching a hundred million users and attracting a reputed USD1 trillion investor interest in its parent company, OpenAI. The race to dominate the generative AI market is accelerating at breakneck speed, inspiring breathless headlines and immense public interest. Welcome to AI provides a rare view into a frontier area of computer science that will change everything about how you live and work. Listen to this book and better understand how to succeed in the AI-enabled future.
Keywords: Artificial intelligence; Intelligence artificielle; artificial intelligence; Audiobooks; Livres audio